The Disney musical on stage and screen critical approaches from 'Snow White' to 'Frozen' - Rodosthenous, George 1973- (London Bloomsbury, 2017)
The Disney Musical: Critical Approaches on Stage and Screen is the first critical treatment of the corporation's hugely successful musicals both on screen and on the stage. Its 13 articles open up a new territory in the critical discussion of the Disney mega-musical, its gender, sexual and racial politics, outreach work and impact of stage, film and television adaptations. Covering early 20th century works such as the first full-length feature film Snow White and the Seven Dwarfs (1937), to The Lion King - Broadway's highest grossing production in history, and Frozen (2013), this edited collection offers a diverse range of theoretical engagements that will appeal to readers of film and media studies, musical theatre, cultural studies, and theatre and performance. The first section employs film theory, semiotics and film music analysis to explore the animated works and their links to the musical theatre genre. The second section addresses various stage versions and considers Disney's outreach activities, cultural value and productions outside the Broadway theatrical arena. The final section focuses on issues of gender and race portraying representations of race, hetero-normativity, masculinity and femininity in Newsies, Frozen, High School Musical, Aladdin and The Jungle Book. The various chapters address these three aspects of the Disney Musical and offer new critical readings of a vast range of important works from the Disney musical cannon including Enchanted, Mary Poppins, Hunchback of Notre Dame, The Lion King and versions of musicals for television in the early 1990s and 2000s.
Introduction -- Disney musicals: on film. Music and the aura of reality in Walt Disney's Snow White and the seven dwarfs (1937) -- Medieval 'beauty' and romantic 'song' in animated Technirama: pageantry, tableau and action in Disney's Sleeping Beauty -- Mary Poppins: a precursor of the feminist musical? -- Musicals in the mirror: Enchanted, self-reflexivity and Disney's sudden boldness -- Disney adaptations: on stage and beyond. Disney as Broadway auteur: the Disney versions of Broadway musicals for television in the late 1990s and early 2000s -- The Hunchback of Notre Dame (1996): too far 'out there'? / Olaf Jubin -- The Lion King: a 'blockbuster feline' on Broadway and beyond -- Not only on Broadway: Disney JR. and Disney KIDS across the USA -- Disney musicals: gender and race. Dancing toward masculinity: Newsies, gender and desire -- 'We're all in this together': being girls and boys in High school musical (2006) -- 'I wanna be like you': negotiating race, racism and orientalism in The jungle book on stage -- Ashman's Aladdin archive: queer orientalism in the Disney renaissance -- 'For the first time in forever': locating Frozen as a feminist Disney musical.
Includes bibliographical references and index.
Keywords: Motion pictures -- United States -- History and criticism; Musicals -- United States -- History and criticism